Standardized Patient Cases for Teaching Tobacco Cessation - John Mahoney; Frank Vitale; David Eibling; Patricia Campbell; Maurice Clifton (Association of American Medical Colleges, 2008)
Abstract Introduction The clinical practice guideline emphasizes that tobacco dependence is a chronic disease. Quitting is a continuous process with time spent in consideration, planning, maintenance, and relapse. In order to teach medical students how to provide comprehensive tobacco cessation counseling, they must learn effective strategies for each stage. This submission includes eight standardized patient (SP) cases and instructions on how each was used in a tobacco cessation counseling training workshop for third-year clerkship students. There are two cases for each of the four stages of change: precontemplation, action, maintenance, and relapse. Methods The workshop begins with a didactic lecture on the physiology of nicotine addiction, behavioral modification techniques, and the pharmacology of nicotine cessation aids. Pairs of students then alternate between interviewing and providing feedback about their partner so that each student interviews and facilitates a patient in each stage. Students have 9 minutes to conduct the interview and counseling, and then receive feedback for 3 minutes. Feedback consists of self-assessment by the interviewing student about things done well, followed by positive reinforcement by the other student and then the SP. The interviewing student reports on what they would have done differently and the SP provides additional constructive feedback. The SP feedback is scripted in the form of a checklist of most important items for that case. Results This has been one of the most successful programs during the third-year medical school curriculum. In the first cohort of students, they ranked the SP encounters to be very helpful in helping them learn to provide smoking cessation counseling, with 85.5% of students rating the encounters a 6 or 7 on a 7-point scale, with 7 being the highest. Students also reported comfort in providing smoking cessation counseling in their preceptors' offices. Students also demonstrated a significant increase in the number of tobacco cessation counseling encounters reported in their clerkship learning logs, beginning immediately after the implementation of this module of curriculum. Discussion The optimal use of these cases requires a working knowledge of SPs, including standard training techniques. The SP cases themselves are ready to be printed and used for training and the accompanying feedback forms are also printer-ready. Learners should be trained in basic interviewing techniques. Ideally, the groups of learners should be matched according to their level within an individual small group for the best SP counseling and feedback experience. These cases may be used alone, but were constructed as part of an overall session on tobacco cessation. A suggested outline for a lecture that would be the introduction for this type of workshop is included, as are suggestions for accompanying tobacco cessation teaching materials that are available from government courses.